AFF4 Predicts the Prognosis of Colorectal Cancer Patients and Suppresses Colorectal Cancer Metastasis via Promoting CDH1 Expression - Fang, Yi; Cao, Hua; Gong, Xiaoyong; Chen, Yanqing; Zhuang, Yugang; Zhou, Shuqin; Chen, Yuanzhuo; Jiang, Yimei; Ji, Xiaopin; Peng, Hu; Jing, Xiaoqian (Frontiers in Oncology, 2022)
Introduction: AF4/FMR2 family member 4 (AFF4) is a core component of super elongation complex (SEC) and regulates the transcription elongation of many genes. AFF4 depletion or amplification is associated with multiple cancers, but its role in colorectal cancer (CRC) has not been investigated so far. Methods: qRT-PCR and western blot analyzed AFF4 expression in the paired clinical CRC tissues. The patients’ overall survival curve was determined by Kaplan-Meier plotter. In vitro experiments, such as cell proliferation, migration and invasion, were used to preliminarily ascertain the role of AFF4 in CRC. A CRC cells liver metastasis animal model was well-established. Livers were harvested and examined histologically by a series of indicators, such as tumor nodules, liver weight, ALT/AST activity and tumor cells identification by hematoxylin-eosin (HE) staining. Results: We firstly examined the expression of AFF4 in colorectal cancer and normal tissues by collected paired CRC tissues and adjacent normal tissues, revealing that AFF4 was significantly downregulated in CRC patients and lower expression of AFF4 was correlated with poor prognosis. Next, we observed that presence or absence of AFF4 in CRC cells had no effect on cancer cell proliferation, while AFF4 depletion significantly promoted the migration or invasion of CRC cells in vitro. Further, we confirmed that AFF4 deficiency enhanced the metastatic capacity of CRC cells in vivo. Mechanistically, we found AFF4 upregulated the transcription of CDH1 gene, which encodes E-cadherin and suppresses the epithelial-mesenchymal transition (EMT). Knockdown of AFF4 interfered with CDH1 transcription, resulting in downregulation of E-cadherin expression and the progression of CRC. Moreover, restored CDH1 expression could rescue the phenotype of CRC cells without AFF4. Conclusions: Collectively, our data demonstrated that AFF4 served as a significant novel regulator of CRC via CDH1 transcriptional regulation and a potential effective therapy target for patients with CRC.